2 - African Diaspora and the Search for Academic Freedom Safe Havens: Outline of a Research Agenda - Zavale, Nelson Casimiro; Langa, Patrício V. (Journal of Higher Education in Africa, 2022)
This article examines assumptions concerning the extent to which being in exile influences academics’ possibilities to exercise academic freedom, particularly when articulating views on African political and social issues that might be inconvenient to the established political authorities. Two main questions are addressed. First, do African academics need to be in diaspora to exercise their academic freedom, including freedom of expression and free speech, particularly beyond the walls of the university and its consecrated freedom of teaching and research? Second, do factors such as disciplinary background, country of origin, reasons for migrating from Africa and period of living in exile influence the propensity of academics in diaspora to publicly express their views on political and social issues in their home countries? The article begins by conceptualising the African diaspora, African academic diaspora, academic freedom and ‘extramural’ academic freedom.